2016
DOI: 10.1111/lamp.12101
|View full text |Cite
|
Sign up to set email alerts
|

Microfinance, Financial Inclusion, and the Rhetoric of Reaction: The Evolution and Limitations of Microfinance in Brazil

Abstract: Several political and academic circles have considered microfinance to be an important tool to promote economic development and the reduction of poverty. It became a worldwide phenomenon, and the practice disseminated in many developing countries such as Brazil. Even as many authors sing the praises of microfinance—in particular the success in developing countries—the actual experience has fallen short. The goal in this article is to provide a critical analysis of the recent practices of microfinance in Brazil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In both countries, state mediation, especially in the late 2000s, was important to fight social issues (Campoli et al, 2020 ; Lustig et al, 2013 ). We argue other LATAM countries should invest in programs like the ones presented here, as social inclusion is necessary for a high-functioning society (Block, 2008 ), and large private banks may not be interested in providing financial services without guarantees and high fees (Schönerwald & Vernengo, 2016 ).…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both countries, state mediation, especially in the late 2000s, was important to fight social issues (Campoli et al, 2020 ; Lustig et al, 2013 ). We argue other LATAM countries should invest in programs like the ones presented here, as social inclusion is necessary for a high-functioning society (Block, 2008 ), and large private banks may not be interested in providing financial services without guarantees and high fees (Schönerwald & Vernengo, 2016 ).…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…Amidst the multitude of factors influencing these issues, the access and usage of financial services have gained the attention of scholars and policymakers. Hence, 'financial inclusion' became an axiom within the literature (Schönerwald & Vernengo, 2016 ). Yet, the current position that financial inclusion has on the international debate on social problems is not accidental.…”
Section: Introductionmentioning
confidence: 99%
“…Zegarra and Wilson [37] found that increases in the size of MFIs can effectively promote their growth. In addition, there are many other factors, such as institution [38], capital structure [39], choice of loan methods [40], age [41], cost [42], efficiency [24], financial inclusion [43], and information technology [23].…”
Section: The Sustainability Evaluation Of Mfismentioning
confidence: 99%
“…Thus, it is quite challenging to determine the financial sustainability of MFIs in the increasingly complex macroeconomic environment. To the best of our knowledge, the majority of the prior studies have evaluated the financial sustainability of MFIs to institutional and governance factors (Gupta & Mirchandani, 2019; Kauffman & Riggins, 2012; Sainz-Fernandez et al, 2018; Schönerwald & Vernengo, 2016). There are quite a few studies that have investigated the financial sustainability of MFIs in the macroeconomic context along with institutional and governance factors (Ahlin et al, 2011; Awaworyi, 2019; Imai et al, 2011; Vanroose, 2007; Xu et al, 2016, 2019).…”
Section: Introductionmentioning
confidence: 99%